Anion-directed supramolecular chemistry modulating the magnetic properties of nanoscopic Mn coordination clusters: From polynuclear high-spin complexes to SMMs - Schmitt, Wolfgang; Zhu, Nian-Yong (My University, 2016)
We report a supramolecular approach to mixed-valent Mn coordination clusters that demonstrates how halide ions can be applied to in fl uence the assembly of distinct tetranuclear building units to produce a number of related Mn coordination clusters with dense core structures that derive from a cuboctahedral arrangement of Mn ions. In all compounds the alignment of the Jahn – Teller axes of the Mn III centers coincides with the positions of the stabilizing chloride ligands. Thus, the relative chloride concentrations in the reaction mixtures allow us to modify the symmetry and magnetic anisotropy of this basic core structures resulting in isotropic polynuclear high-spin complexes at high Cl − concentrations and Single- Molecule Magnets at lower relative Cl − concentrations
PUBLISHED
Export Date: 13 December 2016
Keywords: mixed-valent Mn coordination clusters; mixed-valent Mn coordination clusters